THE SCOPE OF THE AUTHORITY OF A JUDGE, AS A MEAN OF ENSURING THE RIGHT TO A FAIR TRIAL IN CRIMINAL PROCEEDINGS (Law and world, 2016)
The analysis shows that the existing regulation of the issues discussed herein cannot be regarded as complete. Despite the fact that international experience varies and different approaches may not be all a matter of reconciliation, it is possible to expand the scope of the power of a judge, in order to protect the right to a fair trial, as one of the fundamental principle of law.